The Correlation between Organizational Commitment of Nurses and the Quality of Hospital Services at Women\'s Hospital of Tehran - Amir Omrani; Omid Khosravizadeh; Behnam Najafi; Samira Alirezaei (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2016)
Background: The present study aimed to determine the asociation between organizational commitment of the nurses and quality of hospital services at Women's Hospital of Tehran.